Evaluation of antimicrobial properties and toxicity of abelmoschus esculentus extract / Nur Dahlia Razali - Razali, Nur Dahlia (Faculty of Applied Sciences, 2016)
The aim for this study is to evaluate the antimicrobial properties of Abelmoschus esculentus methanolic leaves extract against two Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa) and two Gram positive bacteria (Staphylococcus aureus and Bacillus substilis) by using disc diffusion method. The minimum inhibitory concentration (MIC) of the methanolic plant extract was tested using macro dilution method. The A.esculentus leaves extract only shows antibacterial activity against Staphylococcus aureus. Then, the result was further tested with MIC, MBC and finally tested for toxicity. The MIC value for S.aureus is 6.25 mg/mL and the MBC value is also 6.25 mg/mL Based on toxicity test on Artemia salina, the Abelmoschus esculentus leaves extract is considered as nontoxic and might be safe to use in human. From the results, the A.esculentus leaves extract might be used as an antimicrobial compound and further studies of this plant is needed.